Charles Kao father of fiber optics - Johnson, Larry (IEEE, 2009)
Charles Kao, the father of fiber-optic communications, was recently awarded a share of the Nobel prize for his work in physics. On October 16th, 2001, Larry Johnson had the opportunity to film an interview with Dr. Kao at the Stanford Park Hotel in Palo Alto, California